ANATOMI SEMBILAN JENIS KAYU KURANG DIKENAL DARI SUKU MELIACEAE (Wood anatomy of nine lesser known species of meliaceae family) - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1993)
Gross and anatomical features of nine lesser known species of the Meliaceae family were observed and described for identification purposes. Fiber dimension were also measured for evaluation of their quality.Five out of nine species observed have decorative appearance, they are: Azadirachta indica, Dysoxylum acutangulum, Dysoxylum caulostachyum, Toona celebica and Toona sinensis. These wood species are therefore recommended for furniture or panelFor identification purposes, several important features, were noted : a) vessels ring poreus in Melia dubia, Toona celebica and Toona sinensis , b) fiber septase in Agalia eusideroxylon, Amoora rubiginosa, Dysoxyluni. acutangulum and Dysoxylum caulostachyum; c).roy homocelular in Aglaia eusideroxylon and Azadirachta indica.Seven species contain fiber with medium qualily for pulp making purposes. Two species contain fiber wilh low quality. No single species contain fiber with high quality.